Association of Sociodemographic and Knowledge about Drug Storage and Expiration Date in Bantul District - Pangarso, Ricardus Noven Wikantri; Kristina, Susi Ari (Rumah Sakit Akademik Universitas Gadjah Mada, 2023)
Storing medicines is a crucial thing to do because storing medicines will affect the stability and effectiveness of the stored medicines. Drug storage is closely related to the expiration time of the drug. The aim of this study was to determine the relationship between sociodemographics and the level of public knowledge about drug storage and drug expiration. This study employed a cross-sectional survey study method. The sample was the residents of Bantul Regency taken using convenience sampling, in the data collection period September-November 2023, with a total of 104 respondents. The questionnaire includes sociodemographic data, storage domain and drug expiration time, distributed on Googleform. Data were analyzed descriptively and using the Chi-square statistical test with p<0.05. The research results showed that 61 (58.7%) respondents had a good level of knowledge of drug storage, 43 (41.3%) and 82 (78.8%) respondents had a good level of knowledge of drug expiration. There is a relationship between gender (p=0.032) and occupation (p=0.041) with the level of knowledge of drug storage and there is a relationship between income (p=0.025) and the level of knowledge of drug expiration. Continuous educational efforts by pharmacists are needed to increase public literacy regarding drug storage.Keywords: Bantul regency, drug expiration,drug store, health literacy, knowledge.